Pengaruh Brand Image, Brand trust Dan Brand Awareness Terhadap Keputusan Pembelian Dettol Hand Sanitizer - M. Mahruz Ali Hs; Hadi Sunaryo; M. Khoirul Anwarodin Brotosuharto (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to analyze the effect of Brand Image, Brand Trust, and Brand Awareness on Purchase Decisions. The research was conducted online by distributing questionnaires via google forms to 85 respondents. Based on the results of the research that has been done, it shows that simultaneously the independent variables (Brand Image, Brand Trust, and Brand Awareness) have a significant effect on the dependent variable (Purchase Decision). Meanwhile, based on the partial test results, the Brand Image, Brand Trust, and Brand Awareness variables have a significant effect on the Dettol Hand Sanitizer Purchase Decision.Dettol descriptively, respondents know the brand image of Dettol hand sanitizer well, respondents also know Dettol brand hand sanitizer well, and respondents know Dettol hand sanitizer brand awareness well, and respondents also know the decision to purchase Dettol brand hand sanitizer products well Keywords: Brand Image, Brand Trust, Brand Awareness, Purchasing Decision